2007
DOI: 10.1007/s10549-007-9560-5
|View full text |Cite
|
Sign up to set email alerts
|

Advanced stages and poorly differentiated grade are associated with an increased risk of HER2/neu positive breast carcinoma only in White women: findings from a prospective cohort study of African-American and White-American women

Abstract: The risk of HER2/neu positive breast carcinoma differs between African-American and White women. For White women only, this risk was statistically significant and increased almost linearly within each TNM stage with grade dedifferentiation. The statistically significantly higher prevalence of "ER(-)/PR(-), HER2(- )" phenotype in African American women potentially is the attributing factor to observed lack of an association between the risk of HER2/neu positive breast carcinoma with advanced stages and poorly d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
36
0

Year Published

2007
2007
2010
2010

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 28 publications
3
36
0
Order By: Relevance
“…A California registry study, although missing nearly 45% of the data to construct triple subtypes, also found the highest prevalence for TNT among AA women (25%), followed by Hispanics (17%), and white women (11%) [28]. Among non-population based studies in Michigan and Philadelphia, higher TNT prevalences among AA women compared to white women have also been noted [29,30]. Similar to previous studies [18,30], we observed no racial differences in the other subtypes, including the other ER-PR-subtype (ER-PR-HER2+).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A California registry study, although missing nearly 45% of the data to construct triple subtypes, also found the highest prevalence for TNT among AA women (25%), followed by Hispanics (17%), and white women (11%) [28]. Among non-population based studies in Michigan and Philadelphia, higher TNT prevalences among AA women compared to white women have also been noted [29,30]. Similar to previous studies [18,30], we observed no racial differences in the other subtypes, including the other ER-PR-subtype (ER-PR-HER2+).…”
Section: Discussionmentioning
confidence: 99%
“…Racial identity was selfreported. The youngest age category (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34) included by necessity a larger range because there were so few cases in this age range as previously described [33]. A poverty index (as an indicator of socio-economic status) was calculated based on the combination of annual household income and the number of people supported by that income, with the annual household income divided by the 1991 national poverty level income for a family of the corresponding size [33,34].…”
Section: Patient-related Factorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Basal-like tumours exhibited higher grade, and tended to be found among younger patients: the prevalence was 16 % in premenopausal and 11 % in postmenopausal patients. Several other investigators reported a higher prevalence of ER-negative, PR-negative[41] or triple negative (ER-negative, PR-negative, HER2-negative)[42] breast cancer in younger African American patients. Most recently, Bauer et al[43] found that in a population-based series of 51 074 incident breast cancer cases identified from the California Cancer Registry (United States), the prevalence of triplenegative breast cancer was 12 %.…”
mentioning
confidence: 95%